Anti-proliferative potentials of Excoecaria agallocha Leaf extract in human breast cancer cell line- an antioxidant enzyme approach - Palagati Rohithkumar Reddy, Rajeswary Hari, Priya Durairaj, Thirunavukarasu palaniyandi (Journal of Applied Pharmaceutical Science, 2023)
In this investigation, an attempt has been made to study the anticancer potential of ethanolic extract of Excoecaria agallocha (EEEA) leaves in terms of their restoration of altered antioxidant status in human breast cancer (MCF-7) cell line. The MCF-7 cell line which was primarily passaged was used for this study. Approximately 4 × 105 cells in each well were divided into four groups and the following treatments were given. Group-I control cells without any treatment, group-II cells were treated with EEEA 25 μg/ml, and group–III cells were treated with EEEA 50μg/ml, respectively. Group-IV cells were treated with doxorubicin (10μg/ml), the positive control used in this study. The treated cells were incubated at 37°C for 24 hours in a CO2 incubator. The enzymatic antioxidants such as catalase (CAT), superoxide dismutase (SOD), glutathione reductase (GR), glutathione S-transferase (GST), and glutathione peroxidase (GPX) as well as non-enzymatic antioxidants such as glutathione, vitamin E, and vitamin C were estimated in the treated MCF-7 cells at the end of incubation. In this study, there was a significant (p < 0.05) increase in CAT and glutathione levels and a decrease in vitamin C, vitamin E, SOD, GR, GST, and GPX levels in the untreated MCF-7 cells. It can be concluded that the ethanolic extract of the EEEA leaf exerts its anticancer activity by modulating the antioxidant enzymes.